Nursing Interventions For Improving Patient Safety In Saudi Hospitals: A Systematic Review (The Review of Diabetic Studies, 2025)
Introduction: Patient safety is universally accepted to be a key measure of healthcare quality, and it is one of the core elements of the national change in Saudi Arabia according to the vision 2030. High-quality, evidence-based, and standardized care are the priorities of this national mandate. Nonetheless, negative attitudes towards safety are still prevalent in Saudi hospitals typically in relation to ineffective policy implementation, the widespread blame-culture, ineffective leadership, and extensive breakdown in communication, especially when it comes to patient handoffs. Since the nursing interventions play a vital role in the reduction of adverse events, it is necessary to synthesize the localized evidence and implement a policy.Study Objective: This systematic review aims to evaluate the evidence from the literature regarding the nursing practice interventions that help to create safer environments for patients in hospitals within Saudi Arabia.Methodology: This review was based on the Preferred Reporting Items of Systematic Reviews and Meta-Analyses (PRISMA 2020). There was a thorough search plan, developed on the basis of the PICOC framework, which was implemented through five large databases (Scopus, Web of Science, PubMed/MEDLINE, Embase, and CINAHL). The studies were to be included in case they present primary empirical data on specific nursing interventions in acute care KSA hospitals with experimental/comparative designs (e.g., pre-post intervention). Articles were screened by two independent reviewers at title/abstract screening and full-text screening.Conclusion: Synthesis showed that structural, high leverage interventions proved the most useful: a single study employing Simplification and Standardization showed a shift in culture to a higher reporting of no harm incidences, with the increase to 28.1 per 1000 patient days. The Forcing Function-based intervention increased patient safety practices and indicators. Lower leverage strategies such as Education and Training on the other hand did not have objective clinical outcome data but did improve staff attitude and knowledge.